Solve the system of equations algebraically. y = –x2 + 3x – 3 x + y = –3

a. (4, –7) and (0, –3)

b. (–4, 7) and (0, 3)

c. (–7, 4) and (3, 0)

d. (4, 7) and (0, –3)

Respuesta :

Answer:

  a.  (4, –7) and (0, –3)

Step-by-step explanation:

Easiest is to check the answer choices.

The constant in the first equation is -3, so we know that (0, -3) is a point on that graph. The sum of those two values is -3, so that is also a point on the graph of the line.

The only two answer choices with (0, -3) as one point are the first and last. The other point in the last answer choice is not on the line (4+7 ≠ -3).

So, the only viable answer choice is the first one.

_____

To solve the system algebraically, you can substitute the expression for y in the first equation into the second equation:

  x + (-x^2 +3x -3) = -3

  -x^2 +4x = 0 . . . . . . . . . add 3

  -x(x -4) = 0 . . . . . . . . . . factor

Solutions are x = 0, x = 4. (These are the values of x that make the factors 0.)

__

Evaluating the second equation to find y is easiest:

  y = -3 -x

For x=0, y = -3.

For x=4, y = -7.

The solutions are (4, -7) and (0, -3).

Ver imagen sqdancefan